The Extent of GVC Engagement in Sub-Saharan Africa - Van Biesebroeck, Johannes; Mensah, Emmanuel B. (World Bank, Washington, DC, 2019)
This paper exploits information from two different datasets to provide a novel and multi-dimensional picture of the engagement of all sub-Saharan African countries in global value chains (GVCs). It documents in detail the nature of the underlying data and the way it is used to construct several indicators of GVC engagement. As a companion to the paper, the data files are made available to interested researchers. While it is impossible to summarize the broad range of experiences that we document, two patterns stand out. First, the level of GVC engagement of most countries in sub-Saharan Africa is rather low, especially for their manufacturing sectors. Second, while there is increased GVC engagement over time in some countries, this pattern is by no means universal. The average engagement for the region over the time period studied (1995-2018) is not even positive on average across countries for several indicators.